Comprehensive analytical assessment of marketing activities of enterprises as a basis for making anti-crisis management decisions - Bahorka, Mariia; Багорка, Марія Олександрівна; Kvasova, Liudmila; Квасова, Людмила Сергіївна; Abramovych, Inna; Абрамович, Інна (Baltija Publishing, 2023)
The purpose of the article is to study the main methods and indicators of comprehensive assessment of the effectiveness of marketing activities (profit, market share, sales volume, etc.), as well as to generalise typical marketing solutions in crisis conditions. The methodological basis of the study was a synthesis of the results of applied research in economics, scientific works of domestic and foreign scientists, which highlighted the basic theories of competitive advantage, competitiveness and marketing management. As a result of the conducted analysis of management problems in the sphere of marketing activity of an organisation, the article marks out the role of the information base for making sound management decisions. The article identifies the areas of comprehensive analysis, namely: study of the market situation, competitive environment, consumer behaviour, macro- and micro-environmental factors. Practical results. Special attention is paid to the complex interaction of marketing and management tools at enterprises in crisis conditions, and if the goal of managing an organisation is to make effective decisions, then the goal of marketing as a business philosophy is the formation of solutions adequate to external conditions, which is especially important during the negative impact of crisis phenomena. The need for the company to use the Internet resource, which allows to establish relations with customers at significantly lower costs, has been justified. Value/originality. A systematisation of typical marketing solutions was carried out depending on the periods of crisis development. Three ways of optimising product promotion costs are proposed. A complex of factors such as: features of the company's mission are highlighted; results of strategic planning; features of the company's marketing strategy; factors of the company's external marketing environment; factors of the company's internal marketing environment, which must be taken into account when making anti-crisis marketing decisions. Метою статті є вивчення основних методів та показників комплексної оцінки ефективності маркетингової діяльності (прибуток, частка ринку, обсяги продажів тощо), а також узагальнення типових маркетингових рішень в кризових умовах. Методологічною основою дослідження було синтез результатів застосованих досліджень в економіці, наукових праць вітчизняних та зарубіжних вчених, які висвітлювали основні теорії конкурентних переваг, конкурентоспроможності та управління маркетингом. В результаті проведеного аналізу проблем управління в сфері маркетингової діяльності організації стаття визначає роль інформаційної бази для прийняття обґрунтованих управлінських рішень. Виділяються напрями комплексного аналізу, а саме: вивчення ринкової ситуації, конкурентного середовища, поведінки споживачів, макро- та мікроекономічних факторів. Практичні результати. Особлива увага приділяється складній взаємодії маркетингових та управлінських інструментів на підприємствах в кризових умовах, і якщо метою управління організацією є прийняття ефективних рішень, то метою маркетингу як філософії бізнесу є формування рішень, адекватних зовнішнім умовам, що особливо важливо під час негативного впливу кризових явищ. Обґрунтована необхідність використання компанією Інтернет-ресурсу, що дозволяє встановлювати відносини з клієнтами за значно менші витрати. Цінність/оригінальність. Проведено систематизацію типових маркетингових рішень залежно від періодів розвитку кризи. Запропоновано три способи оптимізації витрат на просування продукції. Виділено комплекс факторів, таких як: особливості місії компанії; результати стратегічного планування; особливості маркетингової стратегії компанії; фактори зовнішнього маркетингового середовища компанії; фактори внутрішнього маркетингового середовища компанії, які повинні бути враховані при прийнятті антикризових маркетингових рішень.
Комплексна аналітична оцінка маркетингової діяльності підприємств як основа для прийняття управлінських рішень у ситуації кризи
Keywords: analytical assessment; аналітична оцінка; marketing activities; маркетингові заходи; enterprise; підприємство; crisis management; антикризове управління; decision; рішення; crisis period; кризовий період